2010
DOI: 10.1007/s11596-010-0123-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of right ventricular global longitudinal function in patients with tetralogy of fallot by two-dimensional ultrasound speckle tracking imaging

Abstract: Quantification of right ventricular (RV) volume and function remains a challenge because of RV complex geometry by conventional echocardiography. The purpose of this study was to assess RV global longitudinal function in patients with tetralogy of Fallot (TOF) by 2-dimensional ultrasound speckle tracking imaging (STI). Thirty-eight patients with TOF were enrolled in this study and divided into child group (n=25) and adult group (n=13) according to age. Thirty-eight age- and sex-matched normal subjects were sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 24 publications
6
16
0
Order By: Relevance
“…9-11 We have reported similar findings in the current cohort. 12 However, the clinical utility of detecting these changes by STE is unknown in this population.…”
Section: Discussionsupporting
confidence: 86%
“…9-11 We have reported similar findings in the current cohort. 12 However, the clinical utility of detecting these changes by STE is unknown in this population.…”
Section: Discussionsupporting
confidence: 86%
“…Previous individual studies have demonstrated a base-to-apex segmental longitudinal strain gradient for the RV in children and adults (13,1820,23,24) and this base-to-apex gradient is reflective in the segmental longitudinal strain meta-analysis (Figure 5). This pattern remains relatively unchanged and may reflect the relative constant geometry of normal heart with maturation.…”
Section: Discussionmentioning
confidence: 85%
“…From the 10 datasets, 6 datasets with 136 patients reported pGLSRs and were included in the meta-analysis of pGLSRs (1315,1720,22), 5 datasets with 116 patients were eligible for the meta-analysis of pGLSRe (1415,1720,22), and 4 datasets with 67 patients were eligible for the meta-analysis of pGLSRa (1720,22). In addition, from the 10 datasets, 5 datasets with 100 patients reported segmental strain measures at the apex, mid and basal ventricular levels of the RVFW, and were analyzed in the meta-analysis of segmental strain (13,16,1820,23,24). The patient characteristics of the included studies are listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations